2011
DOI: 10.1002/adem.201100018
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Foams – A New Approach for Multifunctional Applications

Abstract: Hybrid foams consist of two different interpenetrating or particulate‐embedded foam‐material classes and, therefore, an enhanced multifunctionality of the material and of the final product can be expected. This paper illustrates the concept of hybrid foams with two selected examples. The cells of an open‐cell steel host‐foam are filled either with a polymer foam or a newly developed direct ceramic foam.The results of compression tests and non‐destructive resonance‐frequency‐damping analyses are presented. An i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…The observed results are in good agreement with published studies on the investigation of metal foams (steel and aluminium foams) impregnated with polymers, such as polyethylene, polyamide, epoxy, expandable polystyrene and polyurethane [11][12][13][14][15]. They report that all of these polymers have a positive effect on the thermal and mechanical parameters of the hybrid foams (e.g.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 1 more Smart Citation
“…The observed results are in good agreement with published studies on the investigation of metal foams (steel and aluminium foams) impregnated with polymers, such as polyethylene, polyamide, epoxy, expandable polystyrene and polyurethane [11][12][13][14][15]. They report that all of these polymers have a positive effect on the thermal and mechanical parameters of the hybrid foams (e.g.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…We believe that in this way it is possible to achieve desired functionality necessary to satisfy requirements of a specific application. Few works have been published in this field [11][12][13][14][15][16][17][18][19], developing and testing hybrid foams based on both metal open-cell structures [12][13][14][15] and closed-cell foams [16][17][18][19]. Herein, further research in this field is presented in which the hybrid foam specimens of different sizes, combining aluminium alloy open-cell foam and two different polymer types, were developed, fabricated, tested and mechanically characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, filling these metallic skeletons with lightweight porous materials can be an interesting alternative to bulk polymers. Reinfried M. et al [14] explored the concept of hybrid foams, which consist of two different interpenetrating embedded foam-material classes. The idea behind the hybrid foams is to overcome the individual shortcomings of single-material foams by combining foams of two different material classes and therefore achieving synergistic property combinations that are relevant and beneficial for future applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, based on the multi-material concept, hybrid structures have been developed by combining the periodic open-cell aluminium foams [20][21][22][23][24][25] or Advanced Pore Morphology (APM) foam elements [26][27][28][29][30] with polymers in which the voids of an open-cell aluminium foams are completely infiltrated with a polymer. Results have demonstrated that the polymer lead to an enhancement of the compressive strength and energy absorption of the resulting hybrid structures compared to the conventional opencell aluminium foams.…”
Section: Introductionmentioning
confidence: 99%